Long-Term Outcomes Following Nonoperative Treatment of Prearthritic or Extra-Articular Hip Pain in Women - Campbell Goldsmith; Jennifer Cheng; Joanna Halpert; Peter Moley (Mary Ann Liebert, 2022)
Introduction: There is an abundance of literature focusing on morphological and surgical outcomes in women with arthritic and prearthritic hip pain. However, no studies have evaluated conservative treatment outcomes, such as physical therapy (PT) and injections, in women with prearthritic or extra-articular hip pain. The purpose of this study is to assess changes in long-term patient-reported outcome measures after nonoperative treatments in women with prearthritic or extra-articular hip pain. Methods: Twenty-nine female patients (35?65 years old) who presented to a single provider between December 1, 2012 and September 1, 2017 for prearthritic or extra-articular hip pain (Tonnis 1 or less) and had baseline patient-reported outcome data (modified Harris Hip Score [mHHS], Hip Outcome Score [HOS] activities of daily living [ADL] and sport scores, International Hip Outcome Tool-33 [iHOT-33]) available from the institutional hip registry were included. Patients underwent nonoperative treatments for intra-articular or extra-articular hip pain. A follow-up questionnaire was prospectively administered at 3?5 years after the baseline visit. Results: Most patients underwent targeted PT (n?=?27; 93%) to treat intra-articular or extra-articular hip pain. Targeted PT can be defined as primarily exercise-based therapy focusing on hip and lumbar stability. Twelve patients (41%) received injections; of these, 11 were also treated with PT. Overall, significant improvements in mHHS, HOS-ADL, and iHOT-33 scores were observed (p?=?0.006, 0.022, and <0.001, respectively). HOS-ADL and iHOT-33 scores improved by a median of 10.3 and 18.0 points, respectively, and were clinically significant. HOS-sport scores also improved but were not statistically significant. There were no differences in patient-reported outcomes between patients who received both PT and injections versus those who received PT, injections, or other treatments. Conclusions: Nonoperative treatments for prearthritic or extra-articular hip pain in women, specifically PT and/or injections, were associated with sustained improvements in patient-reported outcomes at 3?5 years postbaseline.